Upaya Meningkatkan Hasil Belajar Sejarah Indonesia Materi Perkembangan Kolonialisme dan Imperialisme Eropa Melalui Model Pembelajaran Diskusi Siswa Kelas XI IPS2 SMA Negeri 1 Candung - Nurmiati Nurmiati (Departement of Mathematics Education, 2022)
This research is motivated by irregularities in learning, starting from students' lack of enthusiasm in learning history which is seen as less active in learning in class. It was found that in learning many students did not listen to what the teacher explained in front of the class, so many students could not repeat what had been explained, for example the teacher asked students to tell stories and so on. From this it is very influential on student learning outcomes at the end of learning. This study aims to obtain information and discuss the Efforts to Improve Learning Outcomes of Indonesian History Material on the Development of European Colonialism and Imperialism Through Discussion Learning Models for Class XI IPS2 Students of SMA Negeri 1 Cdungung. This research is included in the type of classroom action research (CAR). The location of this research is at SMAN 1 CKL, Agam Regency, West Sumatra Province. The time for this research to be carried out was in the odd semester of the 2019/2020 school year which began in July 2019. The subjects in question in this study were 18 students of class XI IPS2 at SMAN 1 Candung. The research procedure consisted of two cycles with four research stages starting from planning, implementing, observing and reflecting. Collecting data in this study using field notes, student worksheets, observation and reflection. The collected data were analyzed using the percentage formula. The results showed that by using the discussion learning model in the subject of Indonesian history on the development of European colonialism and imperialism, it could improve student learning outcomes for class XI IPS2 SMA Negeri 1 Cdungung. This can be seen from the increase in student learning outcomes and student learning completeness from the pre-cycle, cycle I and cycle II